EVALUATION OF STABILITY OF CAROTENOIDS AND ANTIOXIDANT ACTIVITY OF NASTURTIUM FLOWERS (Tropaeolum majus L.) IN SPRAY-DRYING MICROENCAPSULATION - Juscamaita Fabián, Luis (2017)
Carotenoids were extracted from the petals of yellow nasturtium flowers (Tropaeolum majus L.) with hexane, chloroform and petroleum ether at 12, 24 and 48 hours; The highest yield was obtained with chloroform at 24 hours, which was purified to be solubilized with olive oil. It was then microencapsulated with maltodextrin and gum arabic. The dispersion was carried to a Mini Spray Dried B-290 at drying temperatures of 130 °C, 150°C and 170 °C; In the microencapsulation the % recovery of total carotenoids was evaluated (p<0.05) due to the interaction of the encapsulating agent and the drying temperature, the highest recovery rates were 74.10 % and 83.76 % At 130 °C and 150 °C respectively, with gum arabic; No difference (p>0.05) was found in antioxidant activity ranging from 393.00 to 470.97 μmol TE/g. shows. With regard to % humidity, % hygroscopicity, bulk density (g/cm3) and % yield difference was evident (p<0.05). In the % solubility no difference (p>0.05) is evident, the microcapsule of carotenoids can be used as functional food